Deep‐sea coral record of human impact on watershed quality in the Mississippi River Basin. Issue 1 (24th January 2014) - Prouty, Nancy G.; Roark, E. Brendan; Koenig, Alan E.; Demopoulos, Amanda W.J.; Batista, Fabian C.; Kocar, Benjamin D.; Selby, David; McCarthy, Matthew D.; Mienis, Furu
Abstract One of the greatest drivers of historical nutrient and sediment transport into the Gulf of Mexico is the unprecedented scale and intensity of land use change in the Mississippi River Basin. These landscape changes are linked to enhanced fluxes of carbon and nitrogen pollution from the Mississippi River, and persistent eutrophication and hypoxia in the northern Gulf of Mexico. Increased terrestrial runoff is one hypothesis for recent enrichment in bulk nitrogen isotope (δ15N) values, a tracer for nutrient source, observed in a Gulf of Mexico deep‐sea coral record. However, unambiguously linking anthropogenic land use change to whole scale shifts in downstream Gulf of Mexico biogeochemical cycles is difficult. Here we present a novel approach, coupling a new tracer of agro‐industrialization to a multiproxy record of nutrient loading in long‐lived deep‐sea corals collected in the Gulf of Mexico. We found that coral bulk δ15N values are enriched over the last 150–200 years relative to the last millennia, and compound‐specific amino acid δ15N data indicate a strong increase in baseline δ15N of nitrate as the primary cause. Coral rhenium (Re) values are also strongly elevated during this period, suggesting that 34% of Re is of anthropogenic origin, consistent with Re enrichment in major world rivers. However, there are no pre‐anthropogenic measurements of Re to confirm this observation. For the first time, an unprecedented record of natural and anthropogenic Re variability is documented through coral Re records. Taken together, these novel proxies link upstream changes in water quality to impacts on the deep‐sea coral ecosystem.